PELAPISAN CABE MERAH DENGAN NANOPARTIKEL KITOSAN UNTUK MENGHAMBAT KEHILANGAN VITAMIN C DAN SUSUT BOBOT - Riskiono Slamet (Jurnal Riset Sains dan Kimia Terapan, 2011)
In this research the possible use of chitosan nanoparticle coating on green peppers (Capsium annuum L) after harvesting and to determined the effect of chitosan nanoparticle coating formulation to control the barrier properties toward water and oxygen.was investigated. Manually green peppers were treated with a solution of 1% ,2% and 3% nanoparticle chitosan and then stored at 200C. The parameters of physcochemical properties such as weight loss and ascorbic acid concentrations, were monitored during storage 4 days until 16 days. Results indicated that the physicochemical properties of weight loss and ascorbic concentration did not show remarkable change during storage period. and the longest storage life 16 The best quality of greeen peppers days were obtained from the chitosan nanoparticle coating at 3% concentration.The results suggest that the biodegradable coating with higher water vapour permeability can be used to maintain the quality and sanitary conditions of freshly harvested green peppers in modified atmosphere packaging. Keywords :chitosan nanoparticle, green pepper, vitamin C, total weight Abstrak Penelitian ini bertujuan untuk menentukan pengaruh konsentrasi nanopartikel kitosan yang terhadap kandungan vitamin C dan susut bobot cabe merah. Cabe merah dilapis dengan larutan nanopartikel kitosan, disimpan pada suhu 200C, dan kandungan vitamin C serta susur bobot diukur setiap 4 hari sekali selama 16 hari. Hasil penelitian menunjukkan bahwa cabe merah yang dilapis dengan larutan yang mengandung nanopartikel kitosan 3%, kehilangan vitamin C sebesar 30% pada hari ke 12, sementara cabe merah yang tidak dilapis, kehilangan vitamin C sebesar 53,8%. Sementara kehilangan susut bobot juga menunjukkan pola yang sama dengan vitamin C. Hasil terbaik diperoleh jika cabe merah dilapis dengan larutan yang mengandung 3% nanopartikel kitosan. kata kunci : nanopartikel kitosan, cabe hijau, vitamin C, jumlah bobot